The Effects of Propofol and Thiopental on Nitric Oxide Production and Release in Erythrocytes - Ulku Arslan; Pinar Ulker; Ahmet Yildirim; Melike Cengiz; Murat Yilmaz; Ayse Gulbin Arici; Emel Gunduz; Ali Sait Kavakli; Arzu Hizay; Oguzhan Arslan; Zeynep Yasemin Tavsanoglu; Nihal Ozturk (Medicina)
Background: Hypotension is a common adverse effect associated with the use of propofol and sodium thiopental. The objective of this study was to examine the impact of thiopental and propofol on erythrocyte (RBC) nitric oxide (NO) synthase activity and RBC-mediated NO release. Methods: A prospective, interventional in vitro trial. Male patients aged between 18 and 45 years with a classification of American Society of Anesthesiologists (ASA) class I, defined as healthy individuals, were included in this study. Venous blood samples (20 mL) were obtained from patients who met the inclusion criteria. Measurements were performed using the specific fluorescent probes for NO and calcium (Ca2+). Propofol and sodium thiopental were added to the suspensions at doses of 100, 250, 500, and 1000 μM and incubated for 30 min. All suspensions were proceeded to flow cytometric analysis. Nitrite/nitrate concentration was measured in the supernatant of RBC suspensions after centrifugation. RBC deformability and aggregation were measured by laser diffraction analysis using an ektacytometer. The primary outcome was to evaluate the effects of sodium thiopental and propofol on RBC-NOS activity. Results: Sodium thiopental caused significant increase in intracellular NO concentrations at all doses studied (p < 0.001). Importantly, the intracellular NO concentration increment was positively correlated with sodium thiopental concentration in the suspensions. The presence of L-N-acetylmethyl-arginine in the experimental medium abolished NO production in RBCs in response to sodium thiopental. Sodium thiopental caused increased nitrite and nitrate levels in the suspension medium in a dose-dependent manner. Incubation with thiopental caused an increase in intracellular free Ca+2 levels while propofol induced no change. Sodium thiopental and propofol caused significant decrement in RBC aggregation. Conclusions: This study presents the initial evidence of augmented RBC-mediated NO production and release in response to sodium thiopental administration. In contrast to the effects observed with sodium thiopental, our results demonstrated that propofol had no impact on RBC-mediated NO production.